2012
DOI: 10.1111/j.1467-629x.2012.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of analyst forecasts and earnings trends on perceptions of management forecast credibility

Abstract: We examine whether analyst forecasts influence investors' perceptions of the credibility of a good news management earnings forecast. We hypothesize that the effect of analyst forecasts will depend on whether the analyst forecast confirms management's forecast and the extent to which management's forecast is consistent with the prior earnings trend. Findings indicate that the positive effect of a confirming analyst forecast is greater when the management forecast is trend inconsistent than when it is trend con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…As they focus on logistics, they also show that the logistics performance can be improved. Also Gaynor and Kelton [14] as well as Rupar [44] focus on the credibility of forecasts. Gaynor and Kelton [14] analyze how different forecasts of firms and analysts are perceived and used by investors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…As they focus on logistics, they also show that the logistics performance can be improved. Also Gaynor and Kelton [14] as well as Rupar [44] focus on the credibility of forecasts. Gaynor and Kelton [14] analyze how different forecasts of firms and analysts are perceived and used by investors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The reason may lie in different fields of application, research methods, or sample data. However, a consensus is that forecasts influence the behavior of decision makers [14] [23][44] [52].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mullainathan and Shleifer () found that competitive media often slant towards reader biases, especially on topics where reader beliefs diverge (such as politically divisive issues). Gaynor and Kelton () find that the positive effect of a confirming analyst forecast is greater when the trend in management forecasts is inconsistent than when it is consistent. Yin and Tan () find that analysts with more optimistic stock recommendations are more likely to be regarded as star analysts by the mass media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also Gaynor and Kelton [14] as well as Rupar [44] focus on the credibility of forecasts. Gaynor and Kelton [14] analyze how different forecasts of firms and analysts are perceived and used by investors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Gaynor and Kelton [14] analyze how different forecasts of firms and analysts are perceived and used by investors. They find that if the firm's forecast is in line with the earnings trend, the analyst's forecast is perceived as less useful.…”
Section: Theoretical Backgroundmentioning
confidence: 99%